2010
DOI: 10.1089/pho.2009.2635
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy with Rose Bengal Induces GroEL Expression inStreptococcus mutans

Abstract: PDT may cause effects similar to those of other stressing conditions in S. mutans, and cell death induced by this treatment reflects its incapacity to protect itself sufficiently against the deleterious effects of PDT with Rose bengal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…To date, several researchers have carried out studies on the PDT effect against streptococcal species associated with dental caries and showed the possibility for targeting these cariogenic bacteria. 2,13,18,19,20,21,22,23 However, the present study is the first to show yet reported a PDT effect on S. mutans using erythrosine and a dental halogen curing unit.…”
Section: Discussionmentioning
confidence: 54%
“…To date, several researchers have carried out studies on the PDT effect against streptococcal species associated with dental caries and showed the possibility for targeting these cariogenic bacteria. 2,13,18,19,20,21,22,23 However, the present study is the first to show yet reported a PDT effect on S. mutans using erythrosine and a dental halogen curing unit.…”
Section: Discussionmentioning
confidence: 54%
“…The first of these studies was performed by Bolean et al [115]. They tested whether the expression of GroEL by Streptococcus mutans was enhanced after APDI with rose bengal.…”
Section: Mechanisms Determining Bacterial Susceptibility To Apdimentioning
confidence: 99%
“…toluidine blue and methylene blue) are classified at the blue broadband and are correctly activated by red lights at 600-660nm that corresponds to complementary wavelenght [29,30]. On this same way, red dyes, such as rose bengal, erythrosine, Photogem/Photosan can be irrdiated with wavelenghts between 400-500 nm that corresponds to the blue light spectrum [31,32].…”
Section: Photodynamic Antimicrobial Chemotherapy In Dentistrymentioning
confidence: 99%